Tourism Experiences Affecting Thai Tourists’ Satisfaction with Cultural Tourism in Chanthaburi Province - Phaluehaspailin, Yuboon; Udomsamak, Pichet; Saraithong, Atchawan (Academic MCU Buriram Journal, 2023)
The purpose of this research were to study the tourism experience affecting the satisfaction of Thai tourists with cultural tourism in Chanthaburi Province employing survey research. Data were collected by questionnaires from 428 Thai tourists who had visited cultural tourism in Chanthaburi province by random method. The research tool was a questionnaire. Statistics used in data analysis were percentage, mean, standard deviation, and multiple regression analysis. The research results found that: Tourism experience affecting satisfaction of Thai tourists with cultural tourism in Chanthaburi Province by Multiple Regression analysis. It was found that all 2 independent variables, namely attraction (β=0.309, p<0.01), and accommodation (β=0.354, p<0.01), had an effect on the satisfaction of Thai tourists with cultural tourism in Chanthaburi Province, and explained the variance in Thai tourists’ satisfaction with tourism. cultural tourism in Chanthaburi province at 67.80 percent (R2 = .678).